Pediatric Pulmonology year in review 2017: Part 3. Issue 8 (27th May 2018) - Ren, Clement L.; Muston, Heather N.; Yilmaz, Ozge; Noah, Terry L.
Abstract: Pediatric Pulmonology publishes original research, reviews, and case reports related to a wide range of children's respiratory disorders. We here summarize the past year's publications in our major topic areas, in the context of selected literature in these areas from other journals relevant to our discipline. This review (Part 3 of a 5‐part series) covers selected articles on asthma, physiology/lung function testing, and respiratory infections.